Frontiers and advances in molecular spectroscopy - Laane, Jaan (Amsterdam Elsevier Science, 2018)
Frontiers and Advances in Molecular Spectroscopy once again brings together the most eminent scientists from around the world to describe their work at the cutting-edge of molecular spectroscopy. Much of what we know about atoms, molecules and the nature of matter has been obtained using spectroscopy over the last one hundred years or so. Going far beyond the topics discussed in Jaan Laane’s earlier book on the subject, these chapters describe new methodologies and applications, instrumental developments and theory, which are taking spectroscopy into still new frontiers. The robust range of topics once again demonstrates the wide utility of spectroscopic techniques. New topics include ultrafast spectroscopy of the transition state, SERS/far-uv spectroscopy, femtosecond coherent anti-Stokes Raman spectroscopy, high-resolution laser induced fluorescence spectroscopy, Raman spectroscopy and biosensors, vibrational optical activity, ultrafast two-dimensional spectroscopy, biology with x-ray lasers, isomerization dynamics and hydrogen bonding, single molecule imaging, spectra of intermediates, matrix isolation spectroscopy and more.--Provided by publisher.
Includes bibliographical references and index
Electronic reproduction
Keywords: Molecular spectroscopy; Electronic books